Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 19524 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Pinus nigra J.F.Arnold", "HasGeospatialIssue is false", "Geometry POLYGON((-40 31,-40 73,72 73,72 31,-40 31))", "Year 1950-2010" ] } The dataset includes 19524 records from 142 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004402-150316153013904/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences